Knowledge, attitude and preventive practice towards leptospirosis and seroprevalence of leptospira antibodies among market workers in Selangor, Malaysia - Samsudin, Suhailah (2017)
Objective: The aim of this thesis is to identify and investigate the knowledge, attitude and practices towards leptospirosis prevention along with seroprevalence of leptospira antibodies. Methodology: A cross sectional study was conducted among 120 market workers in four urban markets in Selangor. Questionnaire surveyed and blood sampled were two important methods used in the study. A questionnaire consists of respondent’s background, risk factors, knowledge, attitude and practice questions related with leptospirosis. The blood sample was collected from market workers with consent in purpose of seroprevalence study. The sera were obtained and Microscopic Agglutination Test (MAT) was used to determine seropositivity of leptospira antibodies among market workers. Validation and reliability of the questionnaire were carried out and proper procedure in the laboratory was done according to standard protocol. Result: The result showed majority of respondents have poor knowledge (91.7%), have unacceptable attitude (60.8%) and have unacceptable practice (72.5%). This study has found that there are 44.2% serum samples positive of leptospiral antibodies. Regression analysis was conducted and the result showed that the respondents who were Malaysian and undertook gardening activity have more likely to have good knowledge. Furthermore, this study showed that respondents who have formal education, undertook cleaning outside house, have exposed to contaminated water having more likely to have good attitude. An adjusted odd ratio shows that respondents who were female, undertook gardening activity, went for travelling, undertook cleaning of business premises and have unacceptable practice score have more likely of having seropositive of leptospiral antibodies. Conclusion: The evidence from this study suggests that comprehensive health education should be conducted among market workers regarding leptospirosis and its prevention as majority of them scored poor knowledge, unacceptable attitude and unacceptable practice.